READING ALOUD SHORT STORIES TO ENHANCE STUDENTS' LITERACY IN ELEMENTARY SCHOOL - Rommel Utungga Pasopati; Alvina Salshabilla Linjani Putri; Anggraeni Ramadhani; Agischa Putri Agil; Sinta Uli Simbolon; Farham Nazhib Hamdani (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
This community service activity aims to enhance students’ literacy skills through the implementation of the Reading Aloud method for elementary school pupils at SDN Kapasari I, conducted by lecturers and students of Universitas Dr. Soetomo. The program was designed to foster students’ reading interest and fluency in English by engaging them in expressive reading activities. The implementation consisted of three stages: initial assessment, service delivery, and evaluation. Documentation techniques were used to collect data throughout the process. Approximately fifty students participated actively in the program. They were encouraged to read selected fables both aloud and silently, record their performances, and present them before their peers. The results showed that the Reading Aloud activity effectively increased students’ motivation, confidence, and fluency in reading English texts. In conclusion, this community service project successfully contributed to improving elementary students’ literacy competence and confidence in public reading performance.